2015
DOI: 10.1017/s146810991400036x
|View full text |Cite
|
Sign up to set email alerts
|

Dynastic Politicians: Theory and Evidence from Japan

Abstract: Link to this article: http://journals.cambridge.org/abstract_S146810991400036X How to cite this article: YASUSHI ASAKO, TAKESHI IIDA, TETSUYA MATSUBAYASHI and MICHIKO UEDA (2015). AbstractDynastic politicians, defined as those whose family members have also served in the same position in the past, occupy a sizable portion of offices in many parts of the world. We develop a model of how dynastic politicians with inherited political advantages affect electoral outcomes and policy choices. Our model predicts that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 28 publications
5
51
0
11
Order By: Relevance
“…Hypothesis 1 stated that political dynasty has a negative effect on local government performance. Based on the regression result on Table 3, hypothesis 1 is supported or otherwise stated, the local government with political dynasty has worse performance than local government without political dynasty, in line with previous result by Asako et al, (2015), Mendoza et al, (2012), and Tusalem & Pe-Aguirre (2013). They found that political dynasty weakens government performance and local economic performance.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Hypothesis 1 stated that political dynasty has a negative effect on local government performance. Based on the regression result on Table 3, hypothesis 1 is supported or otherwise stated, the local government with political dynasty has worse performance than local government without political dynasty, in line with previous result by Asako et al, (2015), Mendoza et al, (2012), and Tusalem & Pe-Aguirre (2013). They found that political dynasty weakens government performance and local economic performance.…”
Section: Resultssupporting
confidence: 86%
“…The political dynasty will reduce the level of regional financial accountability (Nuritomo & Rossieta, 2014). It also negatively affect the management of public funds, hampering economic development and weaken the elections competitiveness (Asako et al, 2015). In the long run, political dynasties also threaten democracy and economic development (Querubin, 2013), centralize political power (Mendoza et al, 2012), and foster long-term clientelist relationships (George & Ponattu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent work on political dynasties has improved our understanding of why such dynasties arise and/or persist, analyses of their economic and political consequences have been slower to emerge (for recent exceptions, see Asako et al, 2015;Braganc ßa et al, 2015;Labonne et al, 2015;Folke et al, 2017;Daniele and Vertier, 2016). Inspired by research on the labour market effects of network-based hiring (Bayer et al, 2008;Durante et al, 2015;Dustmann et al, 2016) and the performance of family firms (Bertrand and Schoar, 2006;Perez-Gonzalez, 2006;Villalonga and Amit, 2006;Bennedsen et al, 2007), this article evaluated the relation between political dynasties and politicians' (formal) human capital.…”
Section: Resultsmentioning
confidence: 99%
“…The few existing studies on the economic consequences of dynasties paint a complex and contradictory picture. Asako et al (2015), for example, find that districts represented by dynastic politicians in Japan have worse economic outcomes, despite receiving relatively more distributive benefits. The reason, they argue, is that dynastic politicians spend the distributive benefits inefficiently.…”
Section: Consequences Of Dynasties In Democraciesmentioning
confidence: 99%